2021
DOI: 10.3892/ol.2021.12646
|View full text |Cite
|
Sign up to set email alerts
|

Xenografts derived from patients with head and neck cancer recapitulate patient tumour properties

Abstract: Rodent models mimic the heterogeneity of head and neck cancer (HNC) malignancies and are used to investigate HNC-associated biomarkers and evaluate drug responses. To assess the utility of patient-derived xenografts (PDXs) as an HNC model, 18 tumour samples were obtained from surgical specimens of patients with HNC and implanted into non-obese diabetic severe combined immunodeficient mice. The histological features of PDXs and corresponding patient samples were compared. Furthermore, the present study investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Our findings regarding the histological stability of PDX tumor tissue through passages are consistent with previous studies, in which it has been demonstrated that histological properties, biomarker expression, and mutational profile are stable through passages [35,[38][39][40]. Therapeutic response to anti-cancer therapy in PDX models has also been shown to resemble the clinical response in matched patients [35,40]. However, it has also been demonstrated that the human stromal composition is only maintained for early passages, after which the murine stroma dominates, suggesting that early passages may be better at resembling the donor tumor [41].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings regarding the histological stability of PDX tumor tissue through passages are consistent with previous studies, in which it has been demonstrated that histological properties, biomarker expression, and mutational profile are stable through passages [35,[38][39][40]. Therapeutic response to anti-cancer therapy in PDX models has also been shown to resemble the clinical response in matched patients [35,40]. However, it has also been demonstrated that the human stromal composition is only maintained for early passages, after which the murine stroma dominates, suggesting that early passages may be better at resembling the donor tumor [41].…”
Section: Discussionsupporting
confidence: 92%
“…Especially, when exploring targets like uPAR, which is expressed on tumor-associated activated stromal cells. Our findings regarding the histological stability of PDX tumor tissue through passages are consistent with previous studies, in which it has been demonstrated that histological properties, biomarker expression, and mutational profile are stable through passages [35,[38][39][40]. Therapeutic response to anti-cancer therapy in PDX models has also been shown to resemble the clinical response in matched patients [35,40].…”
Section: Discussionsupporting
confidence: 91%